Information rules : a strategic guide to the network economy - Shapiro, Carl (Harvard Business School P. BostonUS, 1999)
Introduces and explains economic concepts necessary for managing the network economy. Examines topics including how to: develop value-maximising strategies for pricing information; plan product lines of information goods; manage information property rights; and identify, quantify and classify the basic sources of switching costs and lock-in. Provides six strategies for waging a successful standards war.